Answer:
18
Step-by-step explanation:
3(2)+2(4)+4=
6+8+4=18
Answer:
no
Step-by-step explanation:
1/7 is positive, -5 is negative. Negative is less than positive
Answer:
(x-3)(x-6)
Step-by-step explanation:
Fill in g into f and simplify:
(x-2)²-5(x-2)+4 =
x² - 4x + 4 - 5x + 10 + 4 =
x² - 9x + 18 =
(x-3)(x-6)
For this case we have the following system of equations:
![y = -4x-23\\-4x-3y = 13](https://tex.z-dn.net/?f=y%20%3D%20-4x-23%5C%5C-4x-3y%20%3D%2013)
We solve by the substitution method:
We substitute the first equation in the second equation:
![-4x-3 (-4x-23) = 13](https://tex.z-dn.net/?f=-4x-3%20%28-4x-23%29%20%3D%2013)
We apply distributive property considering that ![- * - = +:](https://tex.z-dn.net/?f=-%20%2A%20-%20%3D%20%2B%3A)
![-4x + 12x + 69 = 13\\8x + 69 = 13](https://tex.z-dn.net/?f=-4x%20%2B%2012x%20%2B%2069%20%3D%2013%5C%5C8x%20%2B%2069%20%3D%2013)
We subtract 69 from both sides of the equation:
![8x = 13-69\\8x = -56](https://tex.z-dn.net/?f=8x%20%3D%2013-69%5C%5C8x%20%3D%20-56)
We divide by 8 on both sides of the equation:
![x = \frac {-56} {8}\\x = -7](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%20%7B-56%7D%20%7B8%7D%5C%5Cx%20%3D%20-7)
We look for the value of the variable y:
![y = -4 (-7) -23\\y = 28-23\\y = 5](https://tex.z-dn.net/?f=y%20%3D%20-4%20%28-7%29%20-23%5C%5Cy%20%3D%2028-23%5C%5Cy%20%3D%205)
Thus, the solution of the system is ![(x, y): (-7,5)](https://tex.z-dn.net/?f=%28x%2C%20y%29%3A%20%28-7%2C5%29)
Answer:
![(x, y): (-7,5)](https://tex.z-dn.net/?f=%28x%2C%20y%29%3A%20%28-7%2C5%29)